2016
DOI: 10.4103/ijmr.ijmr_712_15
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity & safety of a single dose of live-attenuated Japanese encephalitis vaccine SA 14-14-2 in adults

Abstract: Background & objectives:Japanese encephalitis (JE) caused by mosquito-borne Flavivirus is one of the leading causes of viral encephalitis in Asia. Control strategies include vector control and human vaccination. Due to lack of immunization programmes in endemic regions, there are still high mortality and morbidity. A live-attenuated SA 14-14-2 JE vaccine (LAJEV) has been licensed and used in Asian countries, including India. We report the assessment of immunogenicity and safety of the vaccine in adults during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The SA14‐14‐2 vaccine is a widely used vaccine included in national immunization programs of several JE‐affected countries [2]. A single dose of SA14‐14‐2 JE vaccine elicits excellent immunogenicity and results in 85–94.5% seroconversion 28 days postvaccination among seronegative individuals [3–5]. Although more than 90% efficacy has been reported at 1‐year postvaccination [6,7], the long‐term efficacy of live‐attenuated SA14‐14‐2 vaccine varies depending on the age group and the demography.…”
Section: Introductionmentioning
confidence: 99%
“…The SA14‐14‐2 vaccine is a widely used vaccine included in national immunization programs of several JE‐affected countries [2]. A single dose of SA14‐14‐2 JE vaccine elicits excellent immunogenicity and results in 85–94.5% seroconversion 28 days postvaccination among seronegative individuals [3–5]. Although more than 90% efficacy has been reported at 1‐year postvaccination [6,7], the long‐term efficacy of live‐attenuated SA14‐14‐2 vaccine varies depending on the age group and the demography.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that a single dose of LAJEV also can be safely administered to adults, generating immunity among both seronegative and naturally seropositive adults. 38 Furthermore, data on the co-administration of LAJEV with MV shows an acceptable short-term safety profile, 15 which may encourage endemic JE countries to revise their national immunization programs to reflect a co-administration of the 2 vaccines as in Sri Lanka. 39 An immunogenicity study examining the co-administration of LAJEV and MV just completed in China, 40 and an immunogenicity and safety study is underway in the Philippines to evaluate the co-administration of LAJEV and the measles-mumpsrubella (MMR) vaccine which pending the results, may turn into an official recommendation for interested countries.…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 40 , 41 Another study on immunogenicity and safety of live attenuated SA14-14-2 JE vaccine in India showed that a single dose induced protective immunity in both JE seronegative and naturally seropositive adults. 42 Almost 95.5% of the participants remained seroprotected at the end of 12-month follow-up. 42 A 30-day follow-up study of live-attenuated SA14-14-2 JE vaccine in 26,239 children showed that the incidence of encephalitis, meningitis, all-cause hospitalization or other serious adverse events was no higher than the control group.…”
Section: Safety Of Japanese Encephalitis Vaccinesmentioning
confidence: 95%
“… 42 Almost 95.5% of the participants remained seroprotected at the end of 12-month follow-up. 42 A 30-day follow-up study of live-attenuated SA14-14-2 JE vaccine in 26,239 children showed that the incidence of encephalitis, meningitis, all-cause hospitalization or other serious adverse events was no higher than the control group. 43 The risk ratios of all-cause hospitalization were 0.70 (95% confidence interval 0.43–1.15), and fever was 0.79 (95% confidence interval 0.56–1.11).…”
Section: Safety Of Japanese Encephalitis Vaccinesmentioning
confidence: 95%